Fluorolabeling of the PPTase-Related Chemical Tags: Comparative Study of Different Membrane Receptors and Different Fluorophores in the Labeling Reactions - Amodeo, Rosy; Convertino, Domenica; Calvello, Mariantonietta; Ceccarelli, Lorenzo; Bonsignore, Fulvio; Ravelli, Cosetta; Cattaneo, Antonino; Martini, Claudia; Luin, Stefano; Mitola, Stefania; Signore, Giovanni; Marchetti, Laura (Frontiers in Molecular Biosciences, 2020)
The set-up of an advanced imaging experiment requires a careful selection of suitable labelling strategies and fluorophores for the tagging of the molecules of interest. Here we provide an experimental workflow to allow evaluation of fluorolabelling performance of the chemical tags target of phosphopantetheinyl transferase enzymes (PPTases), once inserted in the sequence of different proteins of interest. First, S6 peptide tag was fused to three different single-pass transmembrane proteins (the tyrosine receptor kinases TrkA and VEGFR2 and the tumor necrosis factor receptor p75NTR), providing evidence that all of them can be conveniently albeit differently labelled. Moreover, we chose the S6-tagged TrkA construct to test eight different organic fluorophores for the PPTase labelling of membrane receptors in living cells. We systematically compared their nonspecific internalization when added to a S6-tag negative cell culture, the percentage of S6-TrkA expressing cells effectively labelled and the relative mean fluorescence intensity, their photostability upon conjugation, and ratio of specific (cellular) versus background (glass-adhered) signal. This allowed to identify which fluorophores are actually recommended for these labelling reactions. Finally, we compared the PPTase labelling of a purified, YBBR-tagged Nerve Growth Factor with two differently charged organic dyes. We detected some batch-to-batch variability in the labelling yield, regardless of the fluorophore used. However, upon purification of the fluorescent species and incubation with living primary DRG neurons, no significant difference could be appreciated in both internalization and axonal transport of the labelled neurotrophins.